2017
DOI: 10.1007/s00436-017-5420-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterization of Toxoplasma gondii in free-range chickens from grocery stores and farms in Maryland, Ohio and Massachusetts, USA

Abstract: Chickens are considered important in the epidemiology of Toxoplasma gondii. Chicken hearts (n = 1185) obtained from grocery stores were tested for T. gondii infection. Antibodies to T. gondii were assayed in fluid removed from the heart cavity using the modified agglutination test (MAT) at 1:5, 1:25, and 1:100 dilutions. MAT antibodies were detected in 222 hearts at 1:5 dilution and 8 hearts at 1:25 dilution, but none were positive at 1:100 dilution. Seropositive (n = 230, 19.4%) chicken hearts were bioassayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Phylogenetic analysis of T. gondii sequences from this study was clustered together with isolates from other studies ( Figure 2 and Figure 3 ). This indicates close genetic relatedness of the isolates, which corroborates previous reports on chickens from the USA [ 54 ] and cats from China [ 55 ]. According to Bontell et al [ 56 ], sexual recombinants of T. gondii in cats are rare in nature, as transmissions commonly occur through carnivorism and scavenging.…”
Section: Discussionsupporting
confidence: 90%
“…Phylogenetic analysis of T. gondii sequences from this study was clustered together with isolates from other studies ( Figure 2 and Figure 3 ). This indicates close genetic relatedness of the isolates, which corroborates previous reports on chickens from the USA [ 54 ] and cats from China [ 55 ]. According to Bontell et al [ 56 ], sexual recombinants of T. gondii in cats are rare in nature, as transmissions commonly occur through carnivorism and scavenging.…”
Section: Discussionsupporting
confidence: 90%
“…It seems plausible that prolonged contact with the ground or litter as well as access to the outdoor area including free-grazing practices typically seen in organic and free-range chicken farming, increases the likelihood of T. gondii infection. As the demand for slow-growth and/or free-range chicken meat keeps increasing (Ying et al 2017), special attention should be paid to T. gondii infections to reduce potential transmission to humans from undercooked meat or other raw preparations like chicken sausages or carpaccio where there might not be sufficient inactivation of the parasite (Schares et al 2018). The majority of published studies referring to free-range chickens include both commercial and hobby/backyard farms, with a range of seroprevalence from 6.6% to 90% (Asgari et al 2009;Cui et al 2010;Zhao et al 2012;Moré et al 2012;Chumpolbanchorn et al2013;Hamidinejat et al 2014;Gebremedhin et al 2014;Magalhães et al 2016;Vismarra et al 2016;Wang et al 2016;ElFadaly et al 2017;Rodrigues et al 2019;Dubey et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In China, Japan, and the USA, recent studies indicated a 10–20% infection rate of quick-frozen chickens [ 85 , 130 , 160 ]. In India, the chicken tissue prevalence is 2.3% and the seroprevalence is around 6.5% [ 130 ], whereas in Brazil the seroprevalence is around 36% [ 128 ]. T. gondii infection may be accompanied by infection from other pathogens of chickens, as Eimeria tenella [ 161 ].…”
Section: Prevalence Of Toxoplasma Gondii In Food P...mentioning
confidence: 99%